Dirty details : the days and nights of a well spouse - Cohen, Marion Deutsche, 1943- (UPCC book collections on Project MUSE., 1996)
In 1977, at the age of 36, Jeffrey Cohen, a physicist at the University of Pennsylvania, was diagnosed with multiple sclerosis. But it wasn't until 10 years later that the ""dirty details"" began, when the disease had progressed to the point where he could not transfer himself out of his wheelchair. That point is where his wife Marion begins her memoir of caregiving: ""If I had to explain it in three words, those words would be 'nights,' 'lifting,' and 'toilet.' And then, if I were permitted to elaborate further, I would continue, 'nights' does not mean lying awake in fear listening fo.